Blaschko-linear lichen striatus type eruption followed by segmental vitiligo in the same site. - Milano, A. (European Journal of Pediatric Dermatology, 2023)
Lichen striatus is a dermatitis distributed along the lines of Blaschko, characteristic of childhood and self-resolving. Segmental vitiligo is an autoimmune disease more frequent in children. The present report presents the case of a 2-year-old girl with a Blaschko-linear eruption of lichen striatus type followed one year later in the same site by segmental vitiligo.